Healthy and sustainable diets: Community concern about the effect of the future food environments and support for government regulating sustainable food supplies in Western Australia. - Harray, A.; Meng, X.; Kerr, Deborah; Pollard, C. (Elsevier BV, 2018)
OBJECTIVE: To determine the level of community concern about future food supplies and perception of the importance placed on government regulation over the supply of environmentally friendly food and identify dietary and other factors associated with these beliefs in Western Australia. DESIGN: Data from the 2009 and 2012 Nutrition Monitoring Survey Series computer-assisted telephone interviews were pooled. Level of concern about the effect of the environment on future food supplies and importance of government regulating the supply of environmentally friendly food were measured. Multivariate regression analysed potential associations with sociodemographic variables, dietary health consciousness, weight status and self-reported intake of eight foods consistent with a sustainable diet. SETTING: Western Australia. SUBJECTS: Community-dwelling adults aged 18-64 years (n?=?2832). RESULTS: Seventy nine per cent of Western Australians were 'quite' or 'very' concerned about the effect of the environment on future food supplies. Respondents who paid less attention to the health aspects of their diet were less likely than those who were health conscious ('quite' or 'very' concerned) (OR?=?0.53, 95% CI [0.35, 0.8] and 0.38 [0.17, 0.81] respectively). The majority of respondents (85.3%) thought it was 'quite' or 'very' important that government had regulatory control over an environmentally friendly food supply. Females were more likely than males to rate regulatory control as 'quite' or 'very' important' (OR?=?1.63, 95% CI [1.09, 2.44], p?=?.02). Multiple regression modeling found that no other factors predicted concern or importance. CONCLUSIONS: There is a high level of community concern about the impact of the environment on future food supplies and most people believe it is important that the government regulates the issue. These attitudes dominate regardless of sociodemographic characteristics, weight status or sustainable dietary behaviours.